2005
DOI: 10.1081/jdi-200056635
|View full text |Cite
|
Sign up to set email alerts
|

Can Cystatin C Be a Better Marker for the Early Detection of Renal Damage in Primary Hypertensive Patients?

Abstract: In this study, we aimed to compare Cystatin C (Cys C) with other traditional glomerular filtration rate (GFR) markers and to evaluate its superiority over them in detecting early renal involvement in patients with primary hypertension. Fifty-one primary hypertensive patients and 29 healthy control subjects, who were similar in terms of age and gender, were included in the study. In all subjects serum levels of Cys C, beta-2 microglobulin, serum creatinine (SCr), uric acid, BUN, albumin; 24 h urinary levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Relatively few previous studies examined the association between cystatin C levels and hypertension 8, 2022 . Among 906 participants in the Heart and Soul Study, Peralta et al observed that systolic blood pressure was linearly associated with cystatin C (approximately 1.2 mm of Hg increase per 0.4 mg/L of cystatin C) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatively few previous studies examined the association between cystatin C levels and hypertension 8, 2022 . Among 906 participants in the Heart and Soul Study, Peralta et al observed that systolic blood pressure was linearly associated with cystatin C (approximately 1.2 mm of Hg increase per 0.4 mg/L of cystatin C) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Among 906 participants in the Heart and Soul Study, Peralta et al observed that systolic blood pressure was linearly associated with cystatin C (approximately 1.2 mm of Hg increase per 0.4 mg/L of cystatin C) 21 . In another case-control study involving 51 primary hypertension cases and 29 healthy control subjects, Ozer et al concluded that cystatin C was more strongly associated with hypertension than other measures related to renal function such as creatinine clearance, serum uric acud, blood urea nitrogen, beta-2-microglobulin and urinary protein excretion 22 . Finally, in the Multi-Ethnic Study of Atheroscolerosis (MESA), Kestenbaum et al reported an overall positive association between serum cystatin C levels and hypertension 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more sensitive indicators of GFR or renal function have been identified in a variety of diverse systemic diseases including nephropathy in type 2 diabetes mellitus (8), hypertensive nephropathy (9), solid organ transplantation (10), and coronary angiopathy (11). Few studies have investigated serum cystatin C as an endogenous marker of renal function in rheumatic diseases other than rheumatoid arthritis (15, 16).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Herget-Rosenthal and his colleagues found that determining cystatin C levels is a more sensitive test for the early detection of renal function impairment or reduced GFR (1). It has been recognized that an increase in serum cystatin C might well reflect changes in renal function or GFR for renal injury in diverse clinical conditions or diseases, including nephropathy associated with type 2 diabetes mellitus (8), hypertensive nephropathy (9), solid organ transplantation (10), and coronary angiopathy (11). …”
Section: Introductionmentioning
confidence: 99%
“…This trial demonstrated that serum cystatin C levels in patients with uncontrolled hypertension were higher than those in patients with controlled and without hypertension, although all groups had normal serum creatinine concentrations. Relatively few previous studies reported an association between serum cystatin C and hypertension (19,(23)(24)(25). Systolic blood pressure and pulse pressure were significantly associated with serum cystatin C concentrations in a previous study, even among patients with normal creatinine clearance (24).…”
Section: Discussionmentioning
confidence: 84%